Impact de l’anthropisation sur la biodiversité et le fonctionnement des écosystèmes marins. Exemple de la Manche-mer du nord - Rachid Amara (VertigO, 2010)
Marine biodiversity is affected by human activities. The United Nations have declared 2010 International Year of Biodiversity to alert the public on the status and consequences of declining biodiversity in the world. In Europe, as everywhere in the world, human population densities are increasing along the coastal areas. This result in a continuous and rapid acceleration of the use of coastal areas and increased pressure on ecosystems and species they contain. The pollution of the sea, of which 80 % comes from human activities from the land, navigation, introduction of invasive species, overfishing, degradation, fragmentation and habitat loss are the factors responsible for the erosion of marine biodiversity. Exacerbated by climate change, human impacts threaten to destroy the delicate balance of marine ecosystems and the biodiversity they contain. The English Channel and the North Sea are a biogeographical crossroads with a great diversity of habitats and high biodiversity. From a fisheries perspective, it is one of the most productive in the world with 5 % of the total catch in the world. Despite this richness, it is a maritime area where conflicts of interests are exacerbated and where human pressures are high mainly because of an industrial coastal developement. Through various examples of recent literature, we will examine the main causes affecting marine biodiversity taking as many possible examples for the English Channel and the North Sea. We will discuss the serious danger of the loss of biodiversity for the ecological balance of the marine environment and the well-being of humanity as well as the necessity to take account of biodiversity in the conduct of human activities, be they economic or other.